Differential risk factor patterns for a positive treadmill test among subjects with and without ultrasound-based fatty liver - Chavez-Tapia, Norberto C.; Tellez-Avila, Felix I.; Valdes-Escarcega, Marisol; Perez-Bautista, Oliver; Lizardi-Cervera, Javier; Méndez-Sanchez, Nahum; Sanchez-Avila, Juan F.; Ramos, Martha H.; Uribe, Misael (Archives of Medical Science, 2009)
Introduction: It is not clear whether the risk factors for CVD in subjects with NAFLD are the same for subjects without NAFLD. We analyze the risk factor patterns for a positive treadmill test in asymptomatic subjects with and without ultrasound-based fatty liver. Material and methods: This was a cross-sectional study in voluntary subjects from January 2005 to January 2007. Adult subjects with alcohol consumption < 20 γ per day and without liver diseases were included. Anthropometric, biochemical, ultrasound imaging, and exercise treadmill testing data were collected. Use of univariate and multivariate analyses identified the variables that predicted a positive exercise treadmill test. Results: One thousand four hundred twenty one subjects were included. The prevalence of metabolic syndrome and NAFLD was 37.3 and 30.2%, respectively. No differences were observed in the positive treadmill test (1.3% in non-NAFLD group vs. 2.3% in NAFLD group, p = 0.176). In subjects with NAFLD, systolic blood pressure ł 130 mm Hg was associated with a positive treadmill test (OR = 4.705, 95% CI 1.285-17.231). In subjects without NAFLD, waist circumference (OR = 8.750, 95% CI 1.830-41.843) and metabolic syndrome (OR = 3.802, 95% CI 1.121-12.987) were factors for a positive treadmill test. Conclusions: Although some evidence demonstrates that subjects with NAFLD had increased risk for CVD, these risk factors are different from those observed in the general population.